Implementasi Dual Identity Anggota Koperasi sebagai Wujud Komitmen Organisasional - Chalimah, Chalimah; Sakhowi, Akhmad (JDM (Jurnal Dinamika Manajemen), 2014)
The purposes of this research was to enhance organizational commitment. Members dual identity in a Koperasi as the owner and the customer at Koperasi is very important to improve organizational commitment since it is easier to achieve the Koperasi success. Implementing members dual identity is becoming the customers. The members participation in Koperasi activities is influenced by many factors such as; individual characteristics, personality, attitude, learning process, ability, perception, and motivation. Those factors will build the organizational commitment and realize the high or low participation. This researchis expected to produce a model whichcan improve organizational commitment and participation of Koperasi members. This study uses SEM (Structural Equation Modeling) as an analytical toolwith 116 respondents as the samples. The results showed that personality gave directly positive and significant influence toward motivation, motivation gave directly significant and positive influence toward organizational commitment, learning process gave directly positive and significant influence toward ability, ability gave directly significant and positive influence toward organizational commitment, organizational commitment gavedirectly significant and positive influence toward member participation.